Comparative study among the patients with different coronary risk factors for detection of asymptomatic coronary artery disease by treadmill test confirmed by coronary angiography - Moumita Saha Paul,; Sovan Mitra,; Uttam Kumar Saha,; Swapnodeep Sarkar, (Asian Journal of Medical Sciences, 2023)
Background: Cardiovascular diseases (CVD) such as ischemic heart disease (IHD) and cerebrovascular accidents such as stroke lead to 17.7 million deaths and are the leading cause of death worldwide. Global Burden of Disease study found that age-standardized CVD death rate in India (272/100,000 population) is much higher than the global average (235/100,000 population). Aims and Objectives: This study aimed to compare among different coronary risk factors like dyslipidemia, diabetes mellitus hypertension (HTN), and obesity which may lead to coronary artery disease (CAD) and early detection of ischemic heart disease by the stress treadmill test (TMT) among the patients having coronary risk factors. Materials and Methods: This is a prospective and observational study among 170 patients of age group 18–60 years having one or more coronary risk factors such as dyslipidemia, HTN, diabetes mellitus, and obesity. Patients with diagnosed IHD and other chronic debilitating diseases were excluded from the study. Results: Out of 170 patients, 153 patients were males and 17 patients were females. Among all these patients, 42 patients were suffering from dyslipidemia, 44 patients were suffering from Type 2 diabetes, 45 patients were suffering from HTN, and 39 patients were having more than one risk factor. All 170 patients with coronary risk factors performed TMT. Out of those patients, 53 were found to be TMT-positive. Binary regression analysis showed among all the selected risk factors, dyslipidemia (P<0.05; odds ratio [OR]-2.104) and HTN (P<0.05; OR-2.159) were found to be significantly associated with the positive outcome of TMT. All 53 TMT-positive patients were selected for CAG. Out of those patients, 37 were found to be suffering from CAD. Binary regression analysis showed among all the selected risk factors, dyslipidemia (P<0.05; OR-1.964) and HTN (P<0.05; OR-2.125) were found to be significantly associated with the positive outcome of CAG. Conclusion: Dyslipidemia and HTN were found to be significantly associated with the TMT-positivity as well as CAD. Diabetes mellitus and obesity were not statistically significant, though OR was more than 1 for both these risk factors.